A Review on Pharmacological Properties and Therapeutic Applications of Zingiber officinale: Review Article (Journal of Pharma Insights and Research, 2025)
The usage of Ginger (Zingiber officinale) has deep roots in traditional healing systems, particularly Ayurveda and Traditional Chinese Medicine. The rhizome's therapeutic potential is mainly due to its phytochemical constituents like gingerols, shogaols, paradols, and essential oils. Modern pharmacological studies have proven the multiple biological activities of ginger, including anti-inflammatory, antioxidant, antiemetic, and immunomodulatory effects. It shows promising results in managing various pathological conditions such as cardiovascular diseases, cancer, metabolic disorders, and inflammatory diseases. Clinical evidence supports its efficacy in treating chemotherapy-induced nausea, postoperative complications, and pregnancy-related morning sickness. The plant's bioactive compounds exhibit variable pharmacokinetic profiles, and affected by preparation methods and formulation techniques. Recent advances in delivery systems and nano-formulations have improved the bioavailability and therapeutic efficacy of ginger compounds. Although substantial evidence supports its safety profile, standardization of dosage regimens and counterweighing of drug interactions remain crucial for effective use of Ginger. The scope of ginger usage is further increased in food preservation and targeted drug delivery systems as reported in the recent literature.